THE IMPACT OF PERCEPTION OF GLASS CEILLING IN ORGANIZATION AND SOCIAL SUPPORT ON MOTIVATION AND ORGANIZATIONAL COMMITMENT - AYUNI, SHEILA PERMATA; HARYADI, HARYADI (INDONESIAN RESEARCH SOCIETY, 2018)
This research takes the title: